Web-based Patient Queuing System and Automatic Notification via WhatsApp Framework Codeigniter - Arnoldus, Arnoldus; Suprihadi, Suprihadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
At present, the benefits of website-based information systems have been widely felt, but there are still many agencies that have not properly utilized the existence of technology. One of the systems that need to be developed in the health sector is giving queue numbers to patients. This study aimed to determine the effectiveness of the web-based patient queuing system and automatic notifications through the WhatsApp framework Codeigniter. The subjects involved in this study were patients who would take a queue number at the clinic. Data collection in the study was carried out by observation and interview methods. The research data were then analyzed using descriptive analysis techniques, namely by describing various findings in the field, which were then linked to the results of previous studies. The system development results show that the system’s success rate for giving queue numbers to patients reaches 100%, and the natrian number reminder system also gets a success percentage of 100%. These results indicate that the queue number system has been successfully developed to help patients search for queue numbers.